P Solubilizing Potential of Some Plant Growth Promoting Bacteria Used as Ingredient in Phosphatic Biofertilizers with Emphasis on Growth Promotion of Zea mays L. Issue 4 (20th April 2020) - Sarikhani, Mohammad Reza; Aliasgharzad, Nasser; Khoshru, Bahman
Abstract: Given the negative environmental impacts of chemical fertilizers, application of phosphate solubilizing bacteria (PSB) as an ecofriendly and safe approach are becoming increasingly popular as substitute to chemical P fertilizers. Nowadays phosphatic microbial fertilizers (PMF) which are formulated by integration of rock phosphate (RP), organic residues, and efficient microorganisms including PSB are being used as biofertilizers to meet plant phosphorus demand. Accordingly, in this study, first P solubilization efficiency of PSBs (including Pseudomonas fluorescens Tabriz, Pseudomonas putida Tabriz, Pseudomonas sp. C16-2O, Enterobacter sp. S16-3, Bacillus megaterium JK6, Bacillus firmus SN1, and Pantoeaagglomerans P5) was checked under in vitro conditions, then the effectiveness of formulated PMFs was evaluated in pot culture using an autoclaved soil. PMFs of seven PSBs were prepared by adding PSB to the substrate consisting of RP, sulfur powder, and bagasse. The results of in vitro investigation on phosphate solubility of PSBs in qualitative (HD/CD) and quantitative procedures in Sperber medium indicated that there were significant differences among the bacteria and different sources of phosphorus. Moreover, P solubility index (HD/CD) showed a good correlation ( r = 0.75, p < 0.05) with P solubility in liquid medium. The highest phosphate solubilization was measured by P . agglomerans P5> Pseudomonas sp. C16-2O > Enterobacter sp. S16-3 > P . putida Tabriz > B. megaterium JK6 > P. fluorescens Tabriz > B. firmus SN1, respectively, and dissolution of phosphorus from tricalcium phosphate (TCP) was higher than from RP. The results obtained from the greenhouse experiments revealed that the application of PMFs on corn had significant effect on fresh and dry weights of shoot and root, and the concentration and content of phosphorus in the root and shoot of corn. The measured parameters in treatments P. agglomerans P5, Pseudomonas sp. C16-2O, Enterobacter sp. S16-3, P . fluorescens and P . putida were significantly higher than control. Although, P5 strain had highest mean in all measured parameters among bacterial strains used in this study, but we introduce new isolated bacteria (S16-3 and C16-2O) along with P5 for further researches. Overall, the two bacteria Enterobacter sp. S16-3 and Pseudomonas sp. C16-2O can be considered because of their positive effects on corn growth [44 and 42% increase in shoot dry weight (SDW) and 1.60- and 1.39-fold increase in root dry weight (RDW), respectively] and P nutrition uptake (both 68% increase in SDW and 1.87- and 1.62-fold increase in RDW, respectively).